A New Derivation for Bradford's Law of Scatter (Paper K) - Mini Devi, B. (Journal of Information and Knowledge, 2013)
The article highlights the significance of Bradford's law in today's information age. The classical law is applied to the toxicology literature collected from the international database, Toxicology Information Online, (TOXLINE), and its validity on that data was tested. The data was found unfit for the law. Hence a new formula is derived and applied which was found fit for the study.